The Surprising Microscopic Wonders from the Depths of Villefranche-sur-Mer - John R. Dolan (Arts et Sciences)
The Institut de la Mer de Villefranche is located near deep Mediterranean waters, and so is well-placed for investigations of the fauna of the deep sea. Shown here are some rare images of living microscopic organisms that populate the deep sea. Each shows a beautiful and complex morphology, and some images show unexpected features.